The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Vol. 1: A. Part II
Editorial Board: Miguel Civil, Ignace J. Gelb, Benno Landsberger, A. Leo Oppenheim, Erica Reiner; Vol. 1: A. Part II: Leo Oppenheim, Editor-in-Charge; Erica Reiner, Editor; Robert D. Biggs, Associate Editor, with the assistance of A. Kirk Grayson, Hans E. Hirsch, Erle V. Leichty, Michael В. Rowton and David B. Weisberg; Assistants to the Editors: Jean Eckenfels and Marjorie Elswick; DM 120.